Persistence of Escherichia coli O157:H12 and Escherichia coli K12 as Non-pathogenic Surrogates for O157:H7 on Lettuce Cultivars Irrigated With Secondary-Treated Wastewater and Roof-Collected Rain Water in the Field - Yin, Hsin-Bai; Gupta, Nidhi; Chen, Chi-Hung; Boomer, Ashley; Pradhan, Abani; Patel, Jitendra (Frontiers in Sustainable Food Systems, 2020)
Treated wastewater (TW) and roof-collected rain water (RW) that meet the required microbial quality as per Food Safety Modernization Act (FSMA) regulation may serve as alternative irrigation water sources to decrease the pressure on the current water scarcity. To evaluate the risk associated with TW and RW irrigation on the fresh produce safety, the effect of TW and RW irrigation on the transfer of Escherichia coli surrogates to different lettuce cultivars grown in the field was investigated. Lettuce cultivars “Annapolis”, “Celinet”, and “Coastline” were grown in the field at the Fulton farm (Chambersburg, PA). Approximately 10 days before harvest, lettuce plants were spray-irrigated with groundwater (GW), TW, or RW containing 6 log CFU ml-1 of a mixture of nalidixic-acid resistant E. coli O157:H12 and chloramphenicol-resistant E. coli K12 in fecal slurry as non-pathogenic surrogates for E. coli O157:H7. On 0, 1, 3, 7 and 10 days-post-irrigation, 4 replicate lettuce leaf samples (30 g per sample) from each group were collected and pummeled in 120 ml buffered peptone water for 2 min, followed by spiral plating on MacConkey agars with antibiotics. Results showed that the recovery of E. coli O157:H12 was significantly greater than the populations of E. coli K12 recovered from the irrigated lettuce regardless of the water sources and the lettuce cultivars. The TW irrigation resulted in the lowest recovery of the E. coli surrogates on the lettuce as compared to the populations of these bacteria recovered from the lettuce with RW and GW irrigation on day 0. The difference in leaf characteristics of lettuce cultivars significantly influenced the recovery of these surrogates on lettuce leaves. Populations of E. coli O157:H12 recovered from the RW-irrigated “Annapolis” lettuce were significantly lower than the recovery of this bacterium from the “Celinet” and “Coastline” lettuce (P<0.05). Overall, the recovery of specific E. coli surrogates from the RW and TW irrigated lettuce was comparable to the lettuce with the GW irrigation, where GW served as a baseline water source. The findings of this study provide critical information in risk assessment evaluation of RW and TW irrigation on lettuce in Mid-Atlantic area.